Regulation of lipid accumulation by AMK-activated kinase in high fat diet–induced kidney injury - Declèves, Anne-Emilie (Kidney Int, 2013)
AMP-activated protein kinase (AMPK) is an important energy sensor that may be critical in regulating renal lipid accumulation. To evaluate the role of AMPK in mediating renal lipid accumulation, C57BL/6J mice were randomized to a standard diet, a high-fat diet, or a high-fat diet plus AICAR (an AMPK activator) for 14 weeks. Renal functional and structural studies along with electron microscopy were performed. Mice given the high-fat diet had proximal tubule injury with the presence of enlarged clear vacuoles, and multilaminar inclusions concurrent with an increase of tissue lipid and overloading of the lysosomal system. The margins of the clear vacuoles were positive for the endolysosomal marker, LAMP1, suggesting lysosome accumulation. Characterization of vesicles by special stains (Oil Red O, Nile Red, Luxol Fast Blue) and by electron microscopy showed they contained onion skin-like accumulations consistent with phospholipids. Moreover, cholesteryl esters and phosphatidylcholine-containing phospholipids were significantly increased in the kidneys of mice on a high-fat diet. AMPK activation with chronic AICAR treatment prevented the clinical and structural effects of high-fat diet. Thus, high-fat diet contributes to a dysfunction of the lysosomal system and altered lipid metabolism characterized by cholesterol and phospholipid accumulation in the kidney. AMPK activation normalizes the changes in renal lipid content despite chronic exposure to lipid challenge.